1998
DOI: 10.1007/bf02914268
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian steroids and serotonin neural function

Abstract: The serotonin neural system originates from ten nuclei in the mid- and hindbrain regions. The cells of the rostral nuclei project to almost every area of the forebrain, including the hypothalamus, limbic regions, basal ganglia, thalamic nuclei, and cortex. The caudal nuclei project to the spinal cord and interact with numerous autonomic and sensory systems. This article reviews much of the available literature from basic research and relevant clinical research that indicates that ovarian steroid hormones, estr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
89
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(93 citation statements)
references
References 239 publications
1
89
0
3
Order By: Relevance
“…Estrogen has also been shown to increase the density of 5HT2A receptors in brain regions associated with mood (Fifa and Fillion, 1992). Taken together, these findings suggest that estrogen can facilitate serotonergic transmission by enhancing serotonin synthesis and/or decreasing serotonin reuptake thereby alleviating depressive symptoms (Bethea et al, 1999). Consistent with this, clinical studies have demonstrated estrogen treatment to have antidepressant effects when administered alone (Klaiber et al, 1996) or in combination with serotonergic antidepressants (Halbreich et al, 1995).…”
Section: Interactions Between Serotonin and Ovarian Hormonesmentioning
confidence: 68%
See 1 more Smart Citation
“…Estrogen has also been shown to increase the density of 5HT2A receptors in brain regions associated with mood (Fifa and Fillion, 1992). Taken together, these findings suggest that estrogen can facilitate serotonergic transmission by enhancing serotonin synthesis and/or decreasing serotonin reuptake thereby alleviating depressive symptoms (Bethea et al, 1999). Consistent with this, clinical studies have demonstrated estrogen treatment to have antidepressant effects when administered alone (Klaiber et al, 1996) or in combination with serotonergic antidepressants (Halbreich et al, 1995).…”
Section: Interactions Between Serotonin and Ovarian Hormonesmentioning
confidence: 68%
“…Serotonergic neurons in the raphe of the rhesus macaque have also been found to contain estrogen inducible progestin receptors thus providing a direct target for the regulation of serotonergic function by ovarian hormones (Bethea, 1993). Ovarian hormones have also been shown to affect numerous factors regulating serotonin synthesis and serotonin levels in the central nervous system (see Bethea et al, 1999 for review). For example, ovarian hormones promote the induction of tryptophan hydroxylase, the rate-limiting enzyme in the synthesis of serotonin, and reduce serotonin reuptake transporter (SERT) mRNA expression in the raphe nuclei.…”
Section: Interactions Between Serotonin and Ovarian Hormonesmentioning
confidence: 99%
“…Serotonergic function is influenced by sex hormones, 26,27 and serotonin system biological variations by gender have been reported. 28 Mice pups prenatally exposed to agents that can alter serotonergic function, including an SSRI, 29,30 showed permanent sex-specific changes in behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be concluded that the 5-HT 1A receptor subtype is a mediator of the antidepressant-like action of E 2 . Evidences in favor of this hypothesis are the results derived from in vitro and in vivo studies, showing that the 5-HT 1A receptor subtype is a target of estrogens and some estrogen-like compounds (Bethea et al, 1998;Biegon et al, 1983;Mize and Alper, 2000;Mize et al, 2001;Raap et al, 2000;Uphouse, 2000). Indeed, Lu and Bethea (2002) demonstrated that E 2 induces the desensitization of 5-HT 1A receptors in the DRN of monkeys.…”
Section: Discussionmentioning
confidence: 99%